2019
DOI: 10.1051/e3sconf/201912524001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of E-learning Websites Using the Webqual Method and Importance Performance Analysis

Abstract: Participant-centered training that uses digital classes leads to changes in the current learning system that focuses on the domain of knowledge. The use of technology in the modern era can be a solution to overcome the issue of expenditure and the quality of educational institutions. The Importance Performance Analysis (IPA) and Webqual methods were chosen in this study because Webqual can translate user opinions in the form of questionnaires and the IPA method is used in managing the results of questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…According to Jundillah et al [14] website quality is a technique of quantifying the website quality based on the last user's perceptions. This method is a development from the SERVQUAL method used to measure service quality [15].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Jundillah et al [14] website quality is a technique of quantifying the website quality based on the last user's perceptions. This method is a development from the SERVQUAL method used to measure service quality [15].…”
Section: Related Workmentioning
confidence: 99%
“…The Importance Performance Analysis (IPA) method aims to quantify the connection between consumer perceptions and product/service quality improvement priorities, known as quadrant analysis [27]. IPA combines the metering of the stage of importance (expectation) and the stage of performance (perception) in a two-dimensional graph that makes it simple to decipher the data and to get practical tips [14]. The IPA graph is divided into four quadrants.…”
Section: Step 2: Webqual With Importance Performance Analysis (Ipa)mentioning
confidence: 99%
“…Measuring the success of services in the digital era requires proper evaluation to obtain an accurate picture of the evaluation. The WebQual method is one method that is considered relevant in measuring the evaluation and performance of digital-based services (Andry et al, 2019;Jundillah et al, 2019). WebQual is a method or technique for measuring website quality based on user perceptions (Faqih et al, 2020).…”
Section: Digitalization Service Qualitymentioning
confidence: 99%
“…The method used with a quantitative move toward, namely multiple linear weakening and showed that variables of usability and services interaction have a significant and positive effect on users approval [5], research that discusses developed a learning method is a mobile-based data structure where students can access materials, referral and applications interrelated to subject devoid of being limited by place and time, whenever and wherever. students arranged that application can optimize the learning process of data structure subject [6], research that discusses determine the quality of web conferencing so that students can enhance the learning process and to know the most significant indicator in the quality of e-Learning and dimensions of usability positive influence to user satisfaction [7], research that discusses the taking perspective of users about the information quality website and 95% self-confidence level is used and the result on the dimensions of information quality (usability quality, information quality, and service interaction quality) has significant influence against to user satisfaction [8], research that discusses the identify and measure involvement of End-User Computing Satisfaction (EUCS) and WebQual 4.0 model consist of usability, information quality and services interaction dimension to user satisfaction on ABC Institution website used quantitative move toward during structural equation modeling (SEM) analysis with assenting factor analysis technique [9], research that discusses the indicated that e-learning service quality was a second-order build comprise of three factors, namely, e-learning system quality, e-learning instructor and course materials quality, and elearning managerial and support service quality [10], research that discusses the evaluate e-learning websites based on the results of the WebQual questionnaire and calculations with the meaning-performance analysis method [11], research that discusses the found that level of significance and level of performance on the e-Questionnaire website that requests to be maximized in ease of use, appearance, and enhancement on the information and communication pages that must be measured by the manager of E-Questionnaire website [12], research that discusses the established IoT-Servqual model with four dimensions (i.e., Privacy, Functionality, Efficiency, and Tangibility) of many service quality models. These dimensions are essential and disposed towards the user leaning of IoT Services [13], research that discusses the quality of the website, such as Lazada.…”
Section: Related Workmentioning
confidence: 99%